Litter of the invasive shrub Rhododendron ponticum (Ericaceae) modifies the decomposition rate of native UK woodland litter. (December 2019) - Jones, Gruffydd Lloyd; Scullion, John; Worgan, Hilary; Gwynn-Jones, Dylan
Highlights: Novel mesocosm design employed to study litter decomposition. Litter mixing with invasive species caused non-additive decomposition. Non-additive decomposition varied between native species. Decomposition rate was strongly correlated with initial litter chemical properties. Leaching of phenolics from invasive litter suppressed microbial respiration. Abstract: Invasive alien plants are a worldwide problem, causing substantial damage to biodiversity as well as economies. Recent studies suggest invasive plants may also alter fundamental ecosystem processes such as nutrient and carbon cycling in soil by depositing chemically distinct leaf litter. Here, we used laboratory microcosms to test whether the chemical properties of Rhododendron ponticum litter, an invasive shrub in Britain, lead to slower decomposition than that of native (or naturalised) species with labile litter ( Acer pseudoplatanus and Fraxinus excelsior ), but not relative to the recalcitrant litter of Quercus petraea . Leading from this, we hypothesised that the labile native litter decomposition rate is reduced when mixed with R. ponticum litter in non-additive responses, with the strength of these responses increasing with the proportion of R. ponticum in litter mixes (25%, 50% and 75% R. ponticum ). Over the incubation period, the decomposition (measured as the microbial respiration rate) of unmixed R. ponticum litter was significantly lower than that of A. pseudoplatanus and F. excelsior, but not Q. petraea . When mixed with R. ponticum (50%), F. excelsior litter decomposition was slowed, whilst no effect was seen for Q. petraea . However, A. pseudoplatanus litter decomposition was enhanced, contrary to expectation. The strength of the non-additive decomposition responses did not vary with different proportions of R. ponticum to the other species, with only the 50% mixtures showing significant non-additive respiration rates. Litter chemical properties were highly associated with decomposition rates, with both phenolic content and C:N ratio negatively correlated with microbial respiration. To test the influence of phenolics on litter decomposition, leachates of R. ponticum litter with phenolics present or removed (via activated carbon) were added to microcosms containing the native species litter. Microbial respiration in F. excelsior microcosms was lower when R. ponticum leachate contained phenolics. For A. pseudoplatanus and Q. petraea litter, no effect of leachate treatment was observed. Our results show that invasive litter chemistry can alter the decomposition of native litter, with the impact varying between species. Altered decomposition rates could cause plant-soil feedbacks, leading to altered soil nutrient concentrations. The novel soil conditions may favour the invader, increasing its dominance, whilst negatively influencing native species possessing greater nutrient demands.